STUDENTS PERCEPTIONS TOWARD GRAMMAR IN ENGLISH CLASSROOM - Mirazna, Mirna Nur; Hikmah, Nur (IKIP Siliwangi, 2019)
The objective of this research focuses on students perceptions toward grammar in the English classroom. This research uses the qualitative descriptive method, the procedure for collecting data uses questionnaire analysis in google forms free online questionnaire. The population is 30 students in class TEI C at SMK TI Pembangunan Cimahi. The sample is 30 students. The results of the data analysis showed that 60% of students stongly agree that grammar in the English classroom important, while the other 40% agree. In addition 96% of students admit that their need to increase English grammar. The most dominant of students perceptions grammar showed to increase skills on grammar 96% of students choose to agree on statements. The findings revealed that students perceived differently toward grammar in the English classroom.CeivedKeywords: Students Perceptions, Grammar English.